PENGARUH KUALITAS PRODUK, CITRA MEREK, HARGA TERHADAP LOYALITAS PELANGGAN CAKE SALAKILO BALIKPAPAN : INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE, PRICE ON CUSTOMER LOYALTY CAKESALAKILO BALIKPAPAN - Azirah, Azirah; Fitriana, Fitriana (Visioner : Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine and test the influence of product quality, brand image, price on customer loyalty for Cake Salakilo Balikpapan. The method and type of research used in this research is a quantitative method. The data sources used are primary and secondary data. The population in this study were Cake Salakilo Balikpapan consumers who purchased more than 3 times a month and a sample of 100 respondents was taken due to the very large population using the Slovin formula. The data collection method uses a questionnaire which is distributed directly to respondents. The data analysis used is multiple linear analysis and classical assumption tests and for data processing using SPSS version 25.  The research results show that: simultaneous testing of product quality variables (X1), brand image (X2) and price (X3) has a positive and significant influence on customer loyalty for Cake Salakilo Balikpapan. Partial testing of the product quality variable (X1) has a positive and significant influence on customer loyalty of Cake Salakilo Balikpapan, the brand image variable (X2) has a positive and significant influence on customer loyalty of Cake Salakilo Balikpapan, and the price variable (X3) has no positive influence and significant impact on Cake Salakilo Balikpapan customer loyalty.